Performance analysis of collision alleviating distributed coordination function protocol in congested wireless networks – a Markov chain analysis. Issue 4 (1st December 2013) - Gottapu, Sasi Bhushana Rao; Tatineni, Madhavi; Kumar, MNVSS
Abstract : IEEE 802.11 is the most popular wireless local area network (WLAN) standard in use. WLANs support broadband multimedia communication and hence providing quality of service requirements such as good throughput and minimum end‐to‐end delay are the two main challenging issues in designing of WLAN protocols for supporting real‐time applications. Until now, several Markov chain models have been developed to evaluate and to enhance the performance of the IEEE 802.11 distributed coordination function (DCF) protocol. However, these models cannot accurately predict the performance of the network. Also, the existing models suffer with high packet collisions resulting in degradation of throughput and end‐to‐end delay particularly under congested environments. This study proposes an exact Markov chain model to accurately predict the performance of the wireless networks. To alleviate the collisions and to avoid channel capture effect, the authors introduce a post‐backoff stage to provide inter packet backoff (IPB) delay between successive packet transmissions. The analysis is carried out by considering the non‐saturated traffic and the impact of channel errors because of Rayleigh fading. Results show significant improvement in throughput and reduction in delay using the proposed model when compared with the existing models.